Pengaruh Kualitas Produk, Harga dan Iklan Terhadap Keputusan Pembelian Mie Instan Merek Indomie PT. Indofood di Lingkungan Mahasiswa Asaindo - Adyba Gozent Sisentia; Sinton L Siahaan (CV. ULIL ALBAB CORP, 2024)
A This study aims to analyze whether Product Quality, Price, and Advertising have an effect on purchasing decisions for Indomie Brand Instant Noodles. The number of samples used in this study was 100 from the population who had purchased indomie brand instant noodles in the ASAINDO environment. The sampling technique used is accidental sampling. The author uses multiple linear regression analysis methods using the Statistical Package for the Social Science version 25 application. The results of this study indicate that product quality has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions, and advertising has a positive and significant effect on purchasing decisions.